FUNGSI SOSIAL ANSAMBEL MUSIK GAMBUS DALAM KEHIDUPAN MASYARAKAT RIAU - Rio Eka Putra (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
Logically naturally social function is the usefulness of a thing for the life of a society and a culture of creativity, taste and human initiative in meeting their needs are complex. Wholly includes knowledge belief, art, customary law, every conversation and habits. In my opinion is one of the traditional arts community culture that has existed and evolved from the first until now, traditional arts became one of the community needs either a primary or secondary. Stringed musical ensamble became the pride of the people of Riau did have game concept and distinctive musical compositions typified the spirit that is rooted in the life of the people of Riau. When talking about the use of music, of course we are referring to the way the music is used or to what is usually the music, either from the instrument itself or its relationship with various other community activities. The social function of music in society with symbols sing a song on someone’s lover, used in this way and other functions globally to pray to a god or singing call (capture) animal. Music used in the right situation and the situation was becoming part of the culture but can have a profound function or may not have a function.Keywords : social function, a stringed instrument ensemble Riau.